Investigating Internal Heat Exchanger Performance in a VCR System with a CO2 and LPG Refrigerant Mixture - Taiwo Elizabeth Oshodin; Kazeem Aderemi Bello; Bukola Olalekan Bolaji; Bayode Julius Olorunfemi; Osagie Jolly Aighovbiosa; Friday Onuh (ABUAD Journal of Engineering Research and Development)
In this study, an attempt was made to develop a cooling system with an internal heat exchanger using a mixture of carbon dioxide (CO2) and liquefied petroleum gas (LPG) as refrigerants to help eliminate the global warming potential and other harmful environmental effects caused by conventional refrigerants'. The CO2 and LPG refrigeration experimental setup was constructed with varying sizes of capillary tubes, a pressure controller, an evaporator, and a gas hob. The working ranges were initially confirmed through exploratory experiments with low-pressure and high-pressure flow circuits, using and without an internal heat exchanger (IHE). The evaporator temperature helped to determine the proportional changes in the coefficient of performance (COP). The REFPROP software design was used to conduct experiments and determine the important process parameters. A confirmation test was performed to validate the expected results of the REFPROP software technique. The results showed that the experiments conducted using IHE had a COP with greater performance levels as follows: mean of 1.398 and SD of 0.367 which is greater than the value of the experiments undertaken without IHE which had a COP performance levels as follows: mean of 0.67 and SD of 0.19. The Paired Samples T-test found these differences to be significant, at p-value < 0.033. The null hypothesis was rejected, hence there is evidence to suggest that the COP of the experiment with IHE is statistically greater than the COP of the experiment without IHE, with a 95% confidence interval of -1.357 and -0.099